2001
DOI: 10.1007/s100530170064
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for trimers evaporation in silver bromide clusters

Abstract: Metastable fragmentation channels of free silver bromide clusters (AgnBrp) + are reported. The large majority release a neutral trimer (AgBr)3. This is interpreted in the frame of ab initio DFT calculations with 19-electron pseudopotential on silver atom. The stability, the structural and electronic properties of (AgnBrp) (+) (n = 6, p = n, n − 1) are examined. The structures of the clusters are different from expected in electrostatic models. The 3D transition has not yet happened: the calculated ground state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
3
16
0
Order By: Relevance
“…[54] Although the energies of the heptamers M 7 X 7 were not known, we can conclude from the present calculation that their dissociation into a trimer + a tetramer is the lowest channel for all species. The large stability of the trimers is in line with previous experiments of fragmentation of metastable silver bromide clusters[15, 16, 56] in which the evaporation of a trimer was found to be the preferred dissociation channel of Ag n Br n ‐p + ( n = 5–14, p = 1–5) clusters.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…[54] Although the energies of the heptamers M 7 X 7 were not known, we can conclude from the present calculation that their dissociation into a trimer + a tetramer is the lowest channel for all species. The large stability of the trimers is in line with previous experiments of fragmentation of metastable silver bromide clusters[15, 16, 56] in which the evaporation of a trimer was found to be the preferred dissociation channel of Ag n Br n ‐p + ( n = 5–14, p = 1–5) clusters.…”
Section: Resultssupporting
confidence: 89%
“…[14] The relative large stability of the trimer was also shown in experiments of fragmentation of metastable clusters in the case of silver bromides. [15, 16] The evaporation of a trimer was found to be the preferred dissociation channel of Ag n Br n ‐p + ( n = 5–14, p = 1–5) clusters. Some theoretical studies,[17, 18] within the framework of the density functional theory (DFT) have investigated the electronic and structural properties of small silver bromide clusters and showed that small stoichiometric clusters Ag n Br n ,with n ≤ 6, adopt cyclic structures and not cube‐like ones as it was supposed hitherto.…”
Section: Introductionmentioning
confidence: 99%
“…In gas phase, an amazing common property of all these compounds is the unusual abundance of trimers in their vapor [4][5][6][7][8][9][10][11][12], although smaller molecules like monomers, and eventually dimers are expected for metal halides. The relative large stability of the trimer was also shown in experiments of fragmentation of metastable clusters in the case of silver bromide [13,14]. The evaporation of a trimer was found to be the preferred dissociation channel of Ag n Br n-p ?…”
Section: Introductionmentioning
confidence: 74%
“…Based on the previous studies, the aim of this work is to further and systematically study the ground state structures and electronic properties of (AgBr) n. It must be pointed out that our initial structures of (AgBr) n are not guessed, but the results of genetic algorithm (GA). Those stable structures in the literatures [20,[22][23][24] are all included in our results of GA, which indicates that our initial structures are reliable, and this method to obtain initial structures can be extended to study large-sized clusters. Those initial structures obtained by GA are further optimized by using DFT method.…”
Section: Introductionmentioning
confidence: 89%
“…The calculation indicated that the most stable geometries of (AgBr) n (n 6 9) were mainly close-packed [22]. Configuration Interaction (CI) calculation was performed to investigate the structures of neutral and single charged (AgBr) n (n 6 2) [23]. The structures and properties of (AgBr) n (n 6 6) were also explored in the framework of DFT/B3LYP with Relativistic Effect Core Pseudopotential (RECP) basis set, in which 19 valence electrons are for Ag and seven valence electrons for Br [24].…”
Section: Introductionmentioning
confidence: 99%